Teatros de guerra: entre los derechos humanos y el arte de Lola Arias - Verónica Perera (Nuevo mundo - Mundos Nuevos, 2019)
During the first years of the democratic transition in Argentina, the dennounciations of human rigths violations committed during the military government absorbed the accounts of the Malvinas war and merged, according to Federico Lorenz, the figure of the victims of the dictatorship with that of the veterans. But the urgencies of the human rights movement were not related to the soldiers of Malvinas. Decades later, the humanitarian narrative entered the activist repertoire of the ex combatants. Following Alicia del Campo on the idea that theater and social theatricalities are cultural scenarios where meanings of recent history are fought over, the article analyzes Lola Arias´ Minefield and Theater of war, and a protest of the Comisión de Familiares de Caídos en Malvinas as stages that display tensions around the human rights discourse and the figure of the victim for activism and the memories of the 1982 war.